A Survey on the Use of Artificial Intelligence Technology and Google Tools for Multilingual Students Sitting and Studying in a Common Classroom - Jha, Saurabh; Mishra, Priti (International Journal of Computer Sciences and Engineering, 2019)
Communication methods and medium of our daily life has been changed by the new emerging Technologies. We can go back in our past and look how communication has got so easier over the years. We are using different types of communication tools with outstanding outputs that we could only imagine some years ago. To communicate with someone in society today, we have so many options present like we can do chat on social media websites, text them, email, or using the traditional approach with new features of calling to a person. Artificial Intelligence is the most popular and advanced technology which we are using now a days in every field of work. The Artificial Intelligence concept and features is used by most of the search engines, websites, smart phones, and websites and smart phone OS to improve their performance. The text to speech and Speech Recognition system made by Google is a very unique feature which helps every type of persons in making effective communication. In this paper we portray a problem statement on Artificial Intelligence Tools usage on a single Classroom of students where each of them are of different countries and admitted in a single course in a university and if any teacher delivers a lectures in his or her class in a single language.